2019
DOI: 10.1021/acs.jmedchem.9b01079
|View full text |Cite
|
Sign up to set email alerts
|

N-Benzyl/Aryl Substituted Tryptanthrin as Dual Inhibitors of Indoleamine 2,3-Dioxygenase and Tryptophan 2,3-Dioxygenase

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1), which catalyzes the initial and rate-limiting step of the kynurenine pathway of tryptophan catabolism, has emerged as a key target in cancer immunotherapy because of its role in enabling cancers to evade the immune system. Tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase 2 (IDO2) catalyze the same reaction and play a potential role in cancer immunotherapy. Starting from our previously discovered tryptanthrin IDO1 inhibitor scaffold, we synthesized novel N-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…These enzymes are first and rate-limiting enzymes of the kynurenine pathway, and implicated in neurodegenerative diseases and tumoral immune resistance; in particular, IDO1 and TDO have been demonstrated as important targets for cancer immunotherapy 23 , 24 , 25 , 26 . Although a number of IDO1 and TDO inhibitors have been reported and several inhibitors are in preclinical development 26 , 27 , 28 , 29 , discovery of new inhibitor chemotypes is still desirable at present. By comprehensive analysis of all reported complex structures for IDO1/TDO and the catalytic mechanisms of the tryptophan substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes are first and rate-limiting enzymes of the kynurenine pathway, and implicated in neurodegenerative diseases and tumoral immune resistance; in particular, IDO1 and TDO have been demonstrated as important targets for cancer immunotherapy 23 , 24 , 25 , 26 . Although a number of IDO1 and TDO inhibitors have been reported and several inhibitors are in preclinical development 26 , 27 , 28 , 29 , discovery of new inhibitor chemotypes is still desirable at present. By comprehensive analysis of all reported complex structures for IDO1/TDO and the catalytic mechanisms of the tryptophan substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The human IDO1 (residues 12–403) and TDO (residues 19–388) 26 , 27 , 28 were cloned into pET28a vectors for expression with N-terminally His 6 -Tagged proteins. IDO1/TDO were overexpressed in E. coli Transetta (DE3) cells at 37 °C using LB medium supplied with 1 mmol/L 5-ALA and 30 μmol/L hemin chloride in a shaker at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…LPS stimulation of KP was performed in C57BL/6 mice as reported with some modifications (Yang et al, 2019). Briefly, Mice were injected i.p with Escherichia coli LPS (5 mg/kg) with a single oral dose of either the vehicle or B37 (10 mg/kg, ig) or EPA (50 mg/kg, ig), respectively.…”
Section: Animal Model and Treatmentmentioning
confidence: 99%
“…Multiple studies have shown that tryptanthrin suppresses tumor growth by modulating various targets, including p38, ERK, PIM1 kinase, and MDR1 [ 17 , 18 , 19 , 20 ]. Recent modifications of tryptanthrin have paved a way to obtain different targeted drugs that include amino-tryptanthrin derivatives such as topoisomerase II (Topo II), N -benzyl tryptanthrin derivatives such as indoleamine 2,3-dioxygenase (IDO), and tryptophan 2,3-dioxygenase (TDO) dual inhibitors ( Figure 1 A) [ 21 , 22 ]. In this study, we report the use of tryptanthrin as the lead compound to synthesize a series of tryptanthrin derivatives with improved anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%